Osgood's semantic differential: a review of the Romanian social sciences literature - Alexandru-Constantin Strunga (Social Sciences and Education Research Review, 2014)
Starting from 1957, with the seminal book of Osgood, Suci and Tannenbaum's ‘Measurement of Meaning', the semantic differential rapidly developed as a complex and subtle research instrument used for measuring social sentiments and attitudes with profound consequences for the social sciences research methodology. The aim of this paper is to analyze how the semantic differential was defined and presented in the Romanian social sciences literature and how it was progressively adopted by the Romanian methodologists from a variety of fields: psychology, sociology and education sciences.